Executive equity incentives and corporate environmental, social and governance performance - Zhang, Shengyang; Li, Zhuo; He, Li (Frontiers in Sustainability, 2025)
Environmental, Social and Governance (ESG) reflects a company’s sustainable development capabilities, and equity incentives, as an important means of internal corporate governance, can enhance ESG performance by alleviating agency conflicts. This study, based on data from Chinese A-share listed companies from 2010 to 2023, using a two-way fixed-effect estimator to probe whether and how a firm’s executive shareholding influences the ESG performance. The results indicate: First, executive shareholding significantly promotes corporate ESG performance, and the conclusion remains robust after a series of robustness tests. Second, mechanism analysis shows that executive shareholding enhances corporate ESG performance by promoting green innovation, encouraging charitable donations, and improving management efficiency. Third, heterogeneity analysis reveals that executive shareholding has a more significant promoting effect on the ESG performance in non-state-owned enterprises, high-pollution enterprises, low-equity concentration enterprises, and non-CEO duality enterprises. The study provide new insights for companies to enhance their ESG performance through internal institutional design and offer important implications for promoting high-quality economic development in China.